"Construcción de una guía deslizante para sierra de la empresa terratécnica S.A. Ubicada en el cantón valencia los Ríos - Peñafiel Soledispa, Johnny Geremias (2019)
This document is structured to build a sliding guide model for saw from Terratécnica. In the first chapter it is explained why it is necessary to develop a new sliding guide model, justifying the necessary requirements, and the process to be followed for the construction. In the second chapter the theoretical basis to understand the